FORMULATION AND EVALUATION OF ENERGY DRINK USING CACTUS FRUIT - Lande Pratibha Santosh,; Korhale Harshad Kisan,; Mohalkar Avdhut Dattatray,; Kale Ishwar Nanasaheb,; Waghmode Vijayshri Ramchandra,; Ankita Arjun Giramkar,; Pratiksha Jalindar Shinde,; Pratiksha Babusha Pawar,; Neha Sunil Garud,; , Dr. Khedkar Amol Navnath, (The Bioscan, 2026)
Betalanin and carotenoids are present within the peel and pulp of various ecotypes which have shown antioxidant Cactus fruit, commonly known as prickly pear, is the edible fruit of the cactus plant belonging to the genus Opuntia. It is widely grow. The cactus pear fruit derived from Cactaceae family plant, morphologically distinct plant families. Cactus fruit is abundantly found in Mexico and the United States, but is also grown in Africa, Madagascar, Australia, Sri Lanka and India. It contains protein, fat, fiber etc., similar to other common fruits. The whole content of free amino acid is more than compared to different fruits, contains high level of serine, g-amino butyric acid, glutamine, proline, arginine and histidine and also contains methionine. It is also rich in calcium and phosphorus.Pigments are found mainly within the fruit, in arid and semi-arid regions of the world, including Mexico, the Mediterranean, the Middle East, Africa, and parts of Asia.The fruit typically has a bright outer skin that can be green, yellow, orange, red, or purple, depending on the variety. Inside, it contains juicy pulp filled with small edible seeds. The taste is mildly sweet and refreshing, often compared to a blend of watermelon and berries.